O sequenciamento verde e seu impacto no valor presente líquido das operações de lavra - Lucas Burini Lobo (2023)
The mining sector has always been of great importance in the social and economic development of the country, however, it is an activity that always gains negative prominence with environmental issues. After major environmental tragedies on Brazilian soil, such as the recent dam failures, a state of alert was installed in the country and especially in regions that have mining activities in their surroundings. As a result, companies are looking for solutions that reduce the environmental impact caused by waste structures. One of the solutions is the disposal of waste in the pit. One of these companies is the Companhia Brasileira de Alumínio (CBA), which has mines located in various regions of the country dedicated to the extraction of bauxite, raw material for the production of aluminum. In Barro Alto - Goiás, where one of its mining operations is located, a project was prepared that allows the disposal of waste in the pit concomitant with the exploitation of the ore. The gains in the ESG agenda (environmental, social and governance) are seen as extremely beneficial, and the support of economic analyzes to support the feasibility of the project is necessary. Mining investment analysis by calculating net present value (NPV) is one of the most commonly used mine optimization steps. This methodology was used in the present work to evaluate the economic impact on the NPV of the mineral enterprise having to be subject to the restriction of waste disposal in the pit. It was then compared what would be the NPV of an optimization made without this restriction and another obeying the sequencing restriction of the waste disposal proposed in that project.